A NEW SLIDING MODE CONTROLLER IMPLEMENTATION ON AN AUTONOMOUS QUADCOPTER SYSTEM - Piquero, Jayson (International journal of automation and smart technology, 2025)
This paper introduces Sliding Mode controller, a non-linear controller, for the implementation of an autonomous quadrotor platform, a non-linear system. The Sliding Mode controller was applied to a PixHawk Flight Controller using the Ardupilot firmware. The simulation testing using SITL shows the effectiveness of the controller before flight. The results imply the improvement when using Sliding Mode Control in comparison to PID controller. The results show that there is a reduction in attitude error when using Sliding Mode Control in comparison with PID control in all simulation and actual hardware results. The robustness of Sliding Mode Control was also tested by adding parameter uncertainties and disturbances to the system. In this study, the root-mean-square error obtained in the Sliding Mode Control is 1.546580%, 0.634243%, and 13.466256% for the roll, pitch, and yaw movements respectively, and the root-mean-square error obtained in the PID control is 2.588324%, 4.553838%, and 18.860183% for the roll, pitch, and yaw movements respectively. This shows that the quadrotor using Sliding Mode Control is less prone to attitude errors.